Evaluate the following integral
∫ 0 ∞ 1 + x 2 0 1 7 1 d x
If your answer comes in the form of b π a csc ( c π ) where a , b , c are positive integers then submit your answer as a + b + c .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
General result:
∫ 0 ∞ 1 + x n 1 d x = n π csc ( n π )
P.S. There is one typo here,
2 0 1 7 1 × 2 ∫ 0 ∞ sin ( z ) − 2 0 1 5 / 2 0 1 7 ⋅ cos ( z ) 2 0 1 5 / 2 0 1 7 d z
should be 2 π .
Log in to reply
Thanks Tapas I have fixed this
In your generalised result is there any restriction on n or it is valid for all n ???
Log in to reply
n must be greater than one for the integral to converge, but yes it is valid for all n>1
Used the same general result!!!! BTW Nice solution!!!
Exact same way as your.
Rewrite there integral in terms of a double integral:
∫ 0 ∞ 1 + x n 1 d x = ∫ 0 ∞ ∫ 0 ∞ e − t ( 1 + x n ) d x d t
Now similar to solving a Gaussian, u = t x n , and the integral becomes
n 1 ∫ 0 ∞ e − u u n 1 − 1 d u ∫ 0 ∞ e − t t n − 1 d t =
By using the definition of the gamma function and Euler's Reflection Formula,
n Γ ( n 1 ) Γ ( 1 − n 1 ) = n sin ( n π ) π
Its great (+1)
Let I = ∫ 0 ∞ 1 + x 2 0 1 7 1 = ∫ 0 1 1 + x 2 0 1 7 1 + ∫ 1 ∞ 1 + x 2 0 1 7 1
Now, let I 1 = ∫ 0 1 1 + x 2 0 1 7 1 = ∫ 0 1 ( 1 − x 2 0 1 7 + x 2 ∗ 2 0 1 7 − x 3 ∗ 2 0 1 7 + . . . ) d x
I 1 = 1 + ∑ 1 ∞ 2 0 1 7 n + 1 ( − 1 ) n
Again let I 2 = ∫ 1 ∞ 1 + x 2 0 1 7 d x = ∫ 1 ∞ x 2 0 1 7 ( 1 + x 2 0 1 7 1 ) d x = ∫ 1 ∞ x 2 0 1 7 d x ( 1 − x − 2 0 1 7 + x − 2 ∗ 2 0 1 7 − . . . )
I 2 = ∑ 1 ∞ 2 0 1 7 n − 1 ( − 1 ) n + 1
So I = I 1 + I 2 = 1 + ∑ 1 ∞ ( 2 0 1 7 n − 1 ( − 1 ) n + 1 − 2 0 1 7 n + 1 ( − 1 ) n + 1 ) = 1 + ∑ 1 ∞ ( ( 2 0 1 7 n ) 2 − 1 2 ( − 1 ) n + 1 _ _ _ _ _ _ _ _ _ _ _ _ _ _ (*)
Since we know sin ( x ) = x ( 1 − π 2 x 2 ) ( 1 − ( 2 π ) 2 x 2 ) . . . taking log and differentiating with respect to x both sides we get
cot ( x ) = x 1 − 2 ∑ 1 ∞ ( n π ) 2 − x x
Using this we can show that ∑ 1 ∞ ( 2 0 1 7 n ) 2 − 1 2 ( − 1 ) n + 1 = − 1 + 2 0 1 7 π ( c o t ( 2 ∗ 2 0 1 7 π ) − c o t ( 2 0 1 7 π ) )
Substituting this in (*) we get I = 2 0 1 7 π ( c o t ( 2 ∗ 2 0 1 7 π ) − c o t ( 2 0 1 7 π ) )
On Simplifying this we get I = 2 0 1 7 π c o s e c ( 2 0 1 7 π ) so answer is 1 + 2 0 1 7 + 2 0 1 7 = 4 0 3 5
Nice 👍 application of gamma , beta function and euler reflection formula
Problem Loading...
Note Loading...
Set Loading...
First substitute x 2 0 1 7 / 2 = tan z = > 2 2 0 1 7 x 2 0 1 5 / 2 d x = sec 2 ( z ) d z = > x 2 0 1 5 / 2 d x = 2 0 1 7 2 sec 2 ( z ) d z = > d x = 2 0 1 7 2 x 2 0 1 5 / 2 1 . sec 2 ( z ) d z = > d x = 2 0 1 7 2 tan ( z ) 2 0 1 5 / 2 0 1 7 1 . sec 2 ( z ) d z
Now using this into the integral
∫ 0 ∞ 1 + x 2 0 1 7 1 d x = ∫ 0 π / 2 2 0 1 7 2 tan ( z ) 2 0 1 5 / 2 0 1 7 1 . sec 2 ( z ) . sec 2 ( z ) 1 d z = 2 0 1 7 1 × 2 ∫ 0 π / 2 sin ( z ) − 2 0 1 5 / 2 0 1 7 . cos ( z ) 2 0 1 5 / 2 0 1 7 d z
Now using definition of Beta-Function we can write
= 2 0 1 7 1 B ( 2 0 1 7 1 , 2 0 1 7 2 0 1 6 )
Then using the property Γ ( z ) Γ ( 1 − z ) = sin ( π z ) π we get the value
= 2 0 1 7 1 Γ ( 1 / 2 0 1 7 ) Γ ( 1 − 1 / 2 0 1 7 ) = 2 0 1 7 π sin ( π / 2 0 1 7 ) 1 = 2 0 1 7 π csc ( π / 2 0 1 7 )